Brain neurokinin-1 receptors in depression and interactions with the serotonin system - Hafizi, S (2009)
Emerging evidence suggests neurokinin-1 receptors (NK1Rs) may be altered in depression and NK1R antagonists may have antidepressant properties. In addition, blockade or deletion of NK1Rs has been shown to increase neuronal firing in the dorsal raphe nucleus suggestive of an interaction with the serotonin (5-HT) system. Against this background, one main aim of this thesis was to investigate anatomical interactions in the rat brain between NK1Rs and the 5-HT system. The second main aim was to use the positron emission tomography (PET) radioligand [18F] SPA-RQ to study NK1Rs in vivo in normal human volunteers and in patients with depression. In the animal studies, immunofluorescence experiments found NK1Rs colocalised with 5-HT1A receptors to a high degree in many forebrain regions, in particular in the medial septum and hippocampus. Colocalisation was also present in the prefrontal cortex, frontal cortex and lateral/basolateral amygdala, but to a lesser degree. NK1Rs were found to mostly colocalise with 5-HT2A receptors in hippocampus only. Colocalisation between NK1Rs and 5-HT1A receptors was much greater than that between NK1Rs and 5-HT2A receptors. In separate experiments, using retrograde tracing combined with immunohistochemistry and light and electron microscopy, NK1Rs were found on the cell bodies of some of the neurons within the lateral habenula and locus coeruleus that project to the dorsal raphe nucleus, but were not found on the cell bodies of afferent neurons in the prefrontal cortex. In the human studies, a comparison of a reversible two-tissue, four rate constants compartment model using plasma input function was made with a transient equilibrium model for the in vivo quantification of NK1Rs in humans using the PET radioligand [18F]SPA-RQ. The regional brain uptake of [18F]SPA-RQ was found to be consistent with the known distribution of NK1Rs: highest in the striatum, moderate in cortex and thalamus and low in the cerebellum. Furthermore, using the transient equilibrium model and a simplified PET imaging protocol with [18F]SPA-RQ, there was no difference in binding potential in any of the brain regions studied between depressed patients, patients recovered from depression and controls. However, a negative correlation was found between age and binding potential for global and regional NK1Rs (in particular, anterior temporal lobe). Collectively these data provide evidence for an interaction between NK1Rs and the 5-HT system at both the presynaptic and postsynaptic levels. In addition, they confirm the utility of the PET radioligand [18F] SPA-RQ for studying NK1Rs in vivo in humans. However, they do not support the idea of altered NK1R numbers in depression.